2019
DOI: 10.1186/s13229-019-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of gender in the perception of autism symptom severity and future behavioral development

Abstract: Background Increasing attention is being paid to the higher prevalence of boys with Autism Spectrum Disorder (ASD) and to the implications of this ratio discrepancy on our understanding of autism in girls. One recent avenue of research has focused on caregiver’s concern, suggesting that autism might present differently in boys and girls. One unexplored factor related to concerns on child development is whether socio-cultural factors such as gender-related expectations influence the evaluation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 41 publications
3
31
0
2
Order By: Relevance
“…Research investigating the discrepancy in prevalence rates of diagnosed autism in males and females has suggested that there is a bias against females with the condition [Lai et al, 2015;Geelhand et al, 2019]. Our findings support this suggestion.…”
Section: Recognition Of Autism In the Vignettessupporting
confidence: 84%
See 3 more Smart Citations
“…Research investigating the discrepancy in prevalence rates of diagnosed autism in males and females has suggested that there is a bias against females with the condition [Lai et al, 2015;Geelhand et al, 2019]. Our findings support this suggestion.…”
Section: Recognition Of Autism In the Vignettessupporting
confidence: 84%
“…population [Geelhand et al, 2019]. It is possible that this is due to an expectancy bias among respondents.…”
Section: Insarmentioning
confidence: 99%
See 2 more Smart Citations
“…First, even with higher ASD prevalence in both sexes, core ASD symptomology are easily presentable in males, and females are too good in camou aging their symptoms, which may result in sex differences in parental concerns after age 5 years [45][46][47][48][49][50]. Second, females experienced less unusual stereotyped and repetitive behaviors than males due to genetic (Y chromosome) and hormonal factors (fetal testosterone) and they have an increased prevalence of internalizing problems [47,51]. Third, females were found to receive lower scores than males particularly on modules 2 and 3 of the Childhood Autism Rating Scale scores (CARS) [52].…”
Section: Discussionmentioning
confidence: 99%